Evaluation of the Quality and Readability of Online Sources on the Diagnosis and Management of Osteochondral Lesions of the Ankle. (December 2021) - Alshaikh, Lamees; Shimozono, Yoshiharu; Dankert, John F.; Ubillus, Hugo; Kennedy, John G.
Objective: Patients frequently use the internet as a source to obtain health information. The purpose of this study was to evaluate the quality and readability of online resources on the diagnosis and treatment of ankle osteochondral lesions (OCLs). Design: Three search terms ("ankle cartilage defect, " "cartilage injury, " "ankle cartilage damage") were entered into 3 search engines (Google, Yahoo, and Bing). The first 20 websites from each search was collected excluding websites intended for health care providers. The quality of the websites were evaluated using the DISCERN instrument, JAMA benchmark, and a Quality rating criteria specific to ankle OCL. The readability was assessed using Flesch Reading Ease (FRE) and Flesch-Kincaid Grade Level (FKGL). Statistical analysis was performed using one-way analysis of variance. Results: A total of 41 websites were reviewed. The mean quality ratings were poor across the assessment tools: DISCERN = 38.5 ± 9.0 (range, 23.7-56.7) out of 80; JAMA = 1.0 ± 1.1 (range, 0-3.3) out of 4; and Quality rating criteria = 11.3 ± 4.6 (range, 4-20.7) out of 24. The mean FRE and FKGL were 40.7 ± 32.0 (range, −152.3 to 60.2) and 13.5 ± 10.8 (range, 8.4-80.7), respectively; higher than the recommended reading level for patients (fifth grade). Conclusions: The quality and readability of credible sources for ankle OCL were poor, which could lead to misinformation. This study should guide the improvement of online information on ankle OCL.